Cardiac Rehabilitation Patient and Organizational Factors: What Keeps Patients in Programs?. Issue 5 (21st October 2013) - Turk‐Adawi, Karam I.; Oldridge, Neil B.; Tarima, Sergey S.; Stason, William B.; Shepard, Donald S.
Abstract : Background: Despite documented benefits of cardiac rehabilitation, adherence to programs is suboptimal with an average dropout rate of between 24% and 50%. The goal of this study was to identify organizational and patient factors associated with cardiac rehabilitation adherence. Methods and Results: Facilities of the Wisconsin Cardiac Rehabilitation Outcomes Registry Project (N=38) were surveyed and records of 4412 enrolled patients were analyzed. Generalized estimating equations were used to account for clustering of patients within facilities. The results show that organizational factors associated with significantly increased adherence were relaxation training and diet classes (group and individual formats) and group‐based psychological counseling, medication counseling, and lifestyle modification, the medical director's presence in the cardiac rehabilitation activity area for ≥15 min/week, assessment of patient satisfaction, adequate space, and adequate equipment. Patient factors associated with significantly increased adherence were aged ≥65 years, the American Association of Cardiovascular and Pulmonary Rehabilitation (AACVPR) high‐risk category, having received coronary artery bypass grafting, and diabetes disease. Non‐white race was negatively associated with adherence. There was no significant gender difference in adherence. None of the baseline patient clinical profiles were associated with adherence including body mass index, total cholesterol, low‐density lipoprotein, high‐density lipoprotein, triglycerides, and blood pressure. Conclusions: Factors associated with adherence to cardiac rehabilitation included both organizational and patient factors. Modifiable organizational factors may help directors of cardiac rehabilitation programs improve patient adherence to this beneficial program.